2022
DOI: 10.13107/jocr.2022.v12.i03.2690
|View full text |Cite
|
Sign up to set email alerts
|

Trochlear Lesion Caused by Suprapatellar Intramedullary Nailing and Treated with Autologous Chondrocytes Implant

Abstract: Introduction:Intramedullary nailing remains the most common method of treatment for tibial shaft fractures. The suprapatellar technique has proven to be useful in gaining and maintaining alignment, especially in proximal one-third tibia shaft fractures. It has been adopted by many surgeons taking trauma call, because it requires less set-up time and allows the surgery to be done with less assistance. We present a case of a femoral trochlea lesion following the placement of a reamed suprapatellar intramedullary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Up to 71% of patients receiving IP nailing complain of anterior knee pain, especially in the kneeling position, possibly due to patellar tendon or infrapatellar nerve violation, no matter whether the paratendinous or transtendinous method is used [ 20 ]. Although the reamers repeatedly go back and forth within the patellofemoral joint during the SP procedure, carrying risks of cartilage damage [ 21 ], the related complications were not reported in our enrolled studies and should be preventable by using a protection sleeve. Chan et al [ 22 ] reported that three out of 11 patients had patellofemoral articular changes found by arthroscopic exam immediately after nailing, but none experienced related joint pain at 12 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 71% of patients receiving IP nailing complain of anterior knee pain, especially in the kneeling position, possibly due to patellar tendon or infrapatellar nerve violation, no matter whether the paratendinous or transtendinous method is used [ 20 ]. Although the reamers repeatedly go back and forth within the patellofemoral joint during the SP procedure, carrying risks of cartilage damage [ 21 ], the related complications were not reported in our enrolled studies and should be preventable by using a protection sleeve. Chan et al [ 22 ] reported that three out of 11 patients had patellofemoral articular changes found by arthroscopic exam immediately after nailing, but none experienced related joint pain at 12 months follow-up.…”
Section: Discussionmentioning
confidence: 99%